Notes on a participatory anad community intervention within the context of cultural diversity - Basagoiti Rodríguez, Manuel; Bru Martín, Paloma (Cuadernos de Trabajo Social, 2012)
The phenomenon of migration has made cultural diversity a fundamental feature of our societies. This new reality, however, evident in the demographic changes in many cities and in the increase of social needs, has not been accompanied by adequate and agile social policies. So, social integration of immigrants in our country has not been easy and, consequently, neither has civic participation.Based on a general contextualization of the evolution of migration and the reflection that increasing cultural diversity in our society has on the public policy of integration, we note in this article (as suggested by the title) some reflections on the importance of local contexts and social participation in the integration of immigrants and, based on work experiences in different areas of Madrid, propose some clues or leads on work to build participatory intervention models in diverse contexts.
Keywords: social integration; social participation; citizenship; community work; immigration